Lisbon mobility simulations for performance evaluation of mobile networks - Vieira, Pedro (2018)
In this paper a novel realistic vehicular mobility model is introduced. It captures the moving-in-groups, conscious travelling, and introduces the concept of smart travelling while following drivers’ social behavior extracted from inquiries and experimental traffic measurements. Under the model, a routing algorithm is considered. The routing algorithm minimizes the distance to a target on a step by step form, in every street crossing. This is done under a hierarchic street level structure that optimizes travel speed and quality. The mobility model was simulated for Lisbon case study and directional statistical results were compared with experimental measurements from Lisbon Municipality control center. The output shows a good correlation between simulated and experimental values.